ARTIFICIAL INTELLIGENCE AND ENTREPRENEURIAL EDUCATION: OPPORTUNITIES FOR CULTURAL TRANSFORMATION IN UNIVERSITY LEARNING ENVIRONMENTS - Niyazov M. Kh. (The Conference Hub, 2025)
This paper explores the transformative potential of artificial intelligence (AI) in the field of entrepreneurial education, focusing on its capacity to promote cultural inclusion and responsiveness within university learning environments.
Keywords: Artificial intelligence, entrepreneurial education, cultural transformation, higher education, adaptive pedagogy, personalization, educational technology.